Prescriptive analytics applied to brace treatment for AIS: a pilot demonstration. Issue 2 (December 2015) - Chalmers, Eric; Hill, Doug; Zhao, Vicky; Lou, Edmond
Abstract Background Prescriptive analytics is a concept combining statistical and computer sciences to prescribe an optimal course of action, based on predictions of possible future events. In this simulation study we investigate using prescriptive analytics to recommend optimal in-brace corrections for braced Adolescent Idiopathic Scoliosis (AIS) patients. The objectives were to estimate the efficacy of these recommendations, ultimately working toward improved brace design protocols. Methods Data was obtained for 90 AIS patients who had finished brace treatment at our center (60 full-time and 30 nighttime braces). Rates of ≥6 degree progression were 53% for daytime and 30% for nighttime braces. A modeling technique previously developed by our group was used to predict these patients' likely treatment outcomes given a range of in-brace corrections – the model was blinded to the true outcomes during this process. Each patient's 'recommended' correction was identified as the least aggressive correction resulting in a desirable predicted outcome. The efficacy of these recommendations was estimated using a technique called "clinical trial simulation" (CTS). This technique used a statistical model to predict progression rate under the model-recommended treatment, and compared it to the true progression rate, observed retrospectively, under the actual treatment. Significance was calculated using a permutation test. Results Model-recommended corrections ranged from 20%-58% for daytime and 65%-130% for nighttime braces, roughly corresponding with previous literature. Interestingly, in 37% of cases the recommended correction was less than that which had actually been applied, suggesting some opportunity for less aggressive (more comfortable) braces without compromising treatment outcome. The CTS estimated 26% fewer progressive cases using the model-recommended in-brace correction, over the actual correction observed retrospectively in the charts (p=0.05). The patients whose correction decreased under the model's recommendation did not show an increased progression rate. Conclusions Optimal correction may be less than the maximum achievable correction. The preliminary results suggest that considering model-generated recommendations during brace fitting could improve outcomes. Future work will expand the system to recommend wear-times as well as corrections, improving its clinical relevance. We envision this pilot demonstration to promote development of model-based decision support in scoliosis treatment, and prompt discussion on its future role.